O filtro da vida: um estudo sobre as modificações sociais no modo de vida dos pacientes renais crônicos em hemodiálise - Mazera, Lucirley (2008)
Chronic renal disease and hemodialysis treatment imposes a big strain and series of limitations to the patient, with regard of the biological, sociological, and psychological perspectives. In this context, practical intervention of the social work is of great need and relevance. The research objective was the understanding of the social modifications in the lifestyle of chronic renal disease patients submitted to hemodialysis treatment from the patient's most significative experiences and introspective reflections about the illness and it's treatment. From our experience and the results obtained from the present investigation, some remarkable aspects are: the public health policies contribution aimed to patients with chronic renal disease, such as rights assurance, based on ANVISA's RDC-154 (2004); the knowledge correlated to the social stigma and to the discriminatory process imposed by the illness-related segregation; the importance of the actuation of the Social Services with the chronic renal patients submitted to hemodialysis, through the Professional Mediation. The methodology used was video recorded Focus Groups. The objective was to understand how the chronic renal patients submitted to hemodialysis experience the treatment and the most significative difficulties during the sickening process. Some empirical categories emerged from the process, such as Disease, Family, Kidney Transplant, Health Teams, Multidisciplinary Team. Willing to discuss the profession essence, we evolved a reflexion based on the emerged categories